Impact of Energy Factors and Digitalization Advancement on Employment: Evidence from Mining, Industry and Electricity Labor Markets - Kaliyeva, Saule; Rakhmetova, Rakhila; Maxyutova, Ainura; Kabylkairatkyzy, Ryszhan; Sadykov, Ilyas (International Journal of Energy Economics and Policy, 2025)
The research aims to assess the impact of energy and digitalization factors on employment in labor markets associated with energy sources. For this purpose, linear and nonlinear autoregressive distributed lag (ARDL & NARDL) models were applied. The following indicators were gathered for this purpose from official domestic and international statistics sources for the years 1998-2023: Internet users, fixed phone subscriptions, mobile cellular subscriptions, and ICT service exports - explanatory variables, Kazakhstan’s crude oil production, average yearly price of Brent crude oil, US dollars per barrel, and CO2 emissions per person (tons). The manufacturing sector, mining and quarrying, and electricity, gas, steam, and air conditioning were the three labor market segments that were examined. According to the study’s findings, employment in these three industries is positively impacted by energy-related variables, but negatively by digitalization variables. This suggests that new job opportunities have been made possible by digitization. The study’s findings also indicate that employment in these industries is somewhat reliant on the supply of oil and its global price. The export of raw materials continues to be the main focus of Kazakhstan’s economy; thus, some policy implications are given in conclusion section. This study adds some empirical value to existing literature on energy labor markets.